Layered liquid crystal nano composition with multiple anti-aging effects and application thereof
By using layered liquid crystal nanocompositions in cosmetics, anti-aging ingredients such as retinol and its derivatives are mixed with other surfactants and polyols in a specific proportion and homogenize them at high pressure, the stability and transdermal absorption of anti-aging ingredients in cosmetics are solved, and higher moisturizing and anti-aging effects are achieved.
Patent Information
- Application Number
- CN202411543574.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the application of anti-aging ingredients such as retinol and its derivatives in cosmetics has problems such as poor stability, sensitivity to photothermality, high irritation, difficulty in formulating fat solubility, and poor transdermal absorption.
Using a layered liquid crystal nanocomposition, a layered liquid crystal structure with similar skin structure is formed by mixing glycolipid emulsifiers, amino acid emulsifiers, retinol and their derivatives, water-soluble actives, ceramide NPs, oils, polyols and water in a specific proportion, and by high-pressure homogenization treatment.
It effectively improves the stability and transdermal absorption of active ingredients, reduces their irritation, and improves moisturizing and anti-aging effects.
Smart Images

Figure CN119564535A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the fields of colloid chemistry, surface chemistry and cosmetics, and specifically relates to a lamellar liquid crystal nanocomposite with multiple anti-aging effects and application thereof. Background Art
[0002] Liquid crystal (LC) is the abbreviation of liquid crystal. It is an intermediate state between solid and liquid, also known as the fourth state of matter. It has the continuity and fluidity of liquid, the anisotropy of single crystal, and is a thermodynamically stable phase.
[0003] Liquid crystal skin care products are widely used in the cosmetics field due to their good skin affinity and unique optical properties. Due to its unique structure, it has many outstanding advantages: excellent water-locking and moisturizing performance. Compared with traditional emulsions, the water evaporation rate of liquid crystals is significantly slowed down. When the water in traditional emulsions evaporates completely, the water content in the liquid crystals is still about 50% of the original water content. This is because in the liquid crystal, there is a layered liquid crystal structure at the water-oil interface, and there is a large amount of bound water between the layers. The release of these bound waters needs to pass through a multi-layer liquid crystal structure, thereby slowing down the evaporation of water; excellent sustained-release performance. Sustained-release refers to the non-constant release of specific active substances in the specified release medium as required, so as to reduce the absorption rate of active substances into the body, prolong the action time of active substances in the system, and improve their utilization rate. Because the layered liquid crystal structure contains a multi-layer liquid crystal network and contains a large amount of bound water, part of the water-soluble substances exist in the external phase water, and part is coated in the combined water of the liquid crystal network. The active substances in the combined water of the liquid crystal network need to pass through multiple layers of obstacles to be released.
[0004] Retinol and its derivatives are fat-soluble vitamins that have the function of regulating the metabolism of the epidermis and stratum corneum. They can resist aging, reduce sebum secretion, lighten epidermal pigments, and protect the epidermal mucosa from bacterial invasion. However, this type of ingredient has certain disadvantages: poor stability and sensitivity to light and heat; high irritation and the need to build tolerance; fat solubility makes it difficult to add to the formula; poor transdermal absorption and low bioavailability.
[0005] Ergothioneine, a natural antioxidant, has excellent free radical scavenging and radiation protection capabilities. Its unique molecular structure enables it to be efficiently recycled in cells, continuously providing antioxidant properties, and is beneficial for protecting cell aging. β-Nicotinamide mononucleotide NMN is a precursor of NAD+. Supplementing NMN can increase the level of NAD+ in the body, improve cell energy metabolism, and protect cells from oxidative damage. Thereby playing an anti-aging role. The biological functions of pyrroloquinoline quinone PQQ are mainly concentrated in two aspects. First, it can support the growth and development of mitochondria and stimulate the rapid growth of human cells; second, it has strong antioxidant properties, which can help scavenge free radicals and reduce cell damage. α-Ketoglutaric acid is a key metabolite of the mitochondrial tricarboxylic acid cycle, which can inhibit protein degradation in muscles; in addition, it can reduce the level of systemic inflammatory cytokines.
[0006] However, since most of the above are water-soluble, their transdermal effects are poor when added directly to the formula, and the existing dosage forms affect their bioavailability. Summary of the invention
[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0009] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a lamellar liquid crystal nanocomposite with multiple anti-aging effects.
[0010] In order to solve the above technical problems, the present invention provides the following technical solution: a lamellar liquid crystal nanocomposition with multiple anti-aging effects, based on the total weight of the composition, comprising:
[0011] Glycolipid emulsifier 0.1%-20%;
[0012] Amino acid emulsifier 0.1%-5%;
[0013] Retinol and its derivatives 0.1%-5%;
[0014] Water-soluble active ingredients 0.01%-5%;
[0015] Ceramide NP 0.01%-1%;
[0016] Oil 10%-20%;
[0017] Polyol 30%-50%;
[0018] Make up to 100% with water.
[0019] As a preferred embodiment of the lamellar liquid crystal nanocomposition of the present invention, the glycolipid emulsifier includes one or more of mannosyl erythritol lipids, cellobiose lipids, disaccharide diglycerides, monoacylglycerols, and galactosyl diglycerides.
[0020] As a preferred embodiment of the lamellar liquid crystal nanocomposition of the present invention, the water-soluble active substance includes one or more of ergothioneine, β-nicotinamide mononucleotide, pyrroloquinoline quinone, and α-ketoglutaric acid.
[0021] As a preferred embodiment of the lamellar liquid crystal nanocomposition of the present invention, the amino acid emulsifier includes one or more of phytosterol / behenyl alcohol / octyldodecyl lauroyl glutamate, phytosterol / octyldodecyl lauroyl glutamate, cholesterol / behenyl alcohol / octyldodecyl lauroyl glutamate, cholesterol lauroyl glutamate, di(laurylamide glutamine) sodium lysine, di(octyldodecyl polyether-5) lauroyl glutamate, and dioctyldodecyl lauroyl glutamate.
[0022] As a preferred embodiment of the lamellar liquid crystal nanocomposition of the present invention, the polyol includes one or more of propylene glycol, butylene glycol, hexylene glycol, pentylene glycol, glycerol and sorbitol.
[0023] As a preferred embodiment of the lamellar liquid crystal nanocomposition of the present invention, the retinol and its derivatives include one or more of retinol, retinol palmitate, retinol propionate, retinol acetate, retinol retinoic acid ester, and hydroxypinacolone retinoic acid ester.
[0024] As a preferred embodiment of the lamellar liquid crystal nanocomposition of the present invention, the oil comprises one or more of behenyl alcohol, cetearyl alcohol, squalane, caprylic capric triglyceride, and octyldodecanol.
[0025] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a lamellar liquid crystal nanocomposition with multiple anti-aging effects, comprising mixing retinol and its derivatives, ceramide NP, and oil, dissolving and stirring at 80 to 90° C. to obtain phase A;
[0026] Mix the glycolipid emulsifier, amino acid emulsifier, water-soluble active ingredient, polyol and water, dissolve and stir evenly at 80-90° C. to obtain phase B;
[0027] Phase B and phase A are mixed evenly, maintained at 80-90° C., stirred at 15000 rpm for initial emulsification, and then high-pressure homogenization is performed at a pressure of 800 bar for 4-5 times to obtain a lamellar liquid crystal nanocomposite.
[0028] Another object of the present invention is to overcome the deficiencies in the prior art and provide a layered liquid crystal nanocomposition with multiple anti-aging effects for use in cosmetics, wherein the cosmetics are selected from one or more of a facial cleanser, a facial mask, a toner or lotion, a cream, and an essence.
[0029] Beneficial effects of the present invention:
[0030] (1) The present invention uses biosurfactants, ceramides and amino acid surfactants to be compounded in a certain ratio to form a lamellar liquid crystal structure similar to the structure of the skin.
[0031] (2) The lamellar liquid crystal nanocomposite with multiple anti-aging effects prepared by the present invention can effectively combine the oil-soluble active substance retinol and its derivatives with water-soluble active substances such as ergothioneine, β-nicotinamide mononucleotide, pyrroloquinoline quinone, and α-ketoglutaric acid, and achieve multi-target anti-aging effects through reasonable proportions.
[0032] (3) The present invention improves the stability and transdermal absorption rate of the active ingredients, reduces their irritation, and enhances their moisturizing and anti-aging effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0034] Figure 1 This is a picture of the liquid crystal structure of the sample prepared in Example 1 of the present invention.
[0035] Figure 2 This is an experiment on the stability of the active ingredient content of the samples in Example 2 of the present invention.
[0036] Figure 3 The particle size stability test results of the samples in Example 2 of the present invention are shown in FIG.
[0037] Figure 4 The following are the results of the skin permeation test of the sample in Example 3 of the present invention.
[0038] Figure 5 This is the test result of collagen content in Example 4 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0041] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0042] The raw materials in the present invention are all common commercially available products.
[0043] Example 1
[0044] Prepare the emulsion according to the raw material ratio in Table 1:
[0045] Preparation method:
[0046] Weigh the oil-soluble raw materials (retinol, ceramide, oil) into a beaker, dissolve and stir evenly at 85°C to obtain phase A;
[0047] Dissolve the water-soluble raw materials (emulsifier, water-soluble active ingredient, polyol, water) at 85°C and stir evenly to obtain phase B;
[0048] Phase B and phase A were mixed evenly in a certain ratio, maintained at 85° C., stirred at 15000 rpm for initial emulsification, and then high-pressure homogenization was performed for 5 times at a pressure of 800 bar to obtain a lamellar liquid crystal nanocomposite.
[0049] Table 1 Raw material ratio table (unit: %)
[0050]
[0051] The results showed that the emulsions prepared from samples 1 and 11 could form obvious lamellar liquid crystal structures; the emulsions prepared from samples 4, 5, and 6 had precipitation and were unstable; and no liquid crystal structure was observed in the emulsions prepared from samples 2, 3, 7, 8, 9, and 10.
[0052] The sample 1 was measured using a polarizing microscope, and the liquid crystal structure diagram obtained is as follows: Figure 1 As shown, an obvious Maltese cross pattern can be observed, proving that a lamellar liquid crystal structure is formed.
[0053] Example 2
[0054] Active ingredient stability test:
[0055] Sample 1 Sample 1 in Example 1 Sample 2 Retinol caprylic capric triglyceride solution (5% by mass)
[0056] Preparation of sample 2: At 50°C, retinol was mixed with caprylic / capric triglyceride in a ratio of 5:95 (mass ratio) and stirred until a transparent solution was obtained.
[0057] Experimental methods:
[0058] The samples were stored at 50°C and the active ingredient content was tested regularly to examine the stability of retinol in the composition. The particle size of the samples was also monitored regularly to examine the particle size stability.
[0059] High performance liquid chromatography was used to determine the retinol content in the samples.
[0060] The results of the active ingredient content stability test are as follows Figure 2 As shown in the results, it can be seen that the stability of retinol in the lamellar liquid crystal nanocomposite is significantly improved compared with free retinol in high temperature stability.
[0061] Particle size stability results are as follows Figure 3 As shown, it can be seen from the results that the particle size of the lamellar liquid crystal nanocomposite is less than 100 nm, and the particle size is stable at high temperature for 4 weeks.
[0062] Example 3
[0063] Transdermal test:
[0064] Sample 1 Sample 1 in Example 1 Sample 2 Aqueous solution of ergothioneine (mass fraction 0.1%)
[0065] Experimental methods:
[0066] In the whole experiment, intact and undamaged pig skin of equal thickness was selected for transdermal experiment. The pig skin was cut into pieces of about 2.5 cm × 2.5 cm in size and placed between the receiving pool and the supply pool of the Franz diffusion cell, with the stratum corneum facing the supply pool.
[0067] The receiving pool contained PBS buffer (pH = 7.4) containing 5% Tween 80;
[0068] Add 2 mL of 4-fold diluted sample to the supply cell;
[0069] The assembled Franz diffusion cell was placed in the transdermal diffusion instrument, and the experimental conditions were set as follows: temperature was 37°C, stirring speed was 400 rpm, and transdermal time was 12 h.
[0070] After the transdermal test, the pigskin was taken out of the diffusion cell, and the residual sample on the surface of the pigskin was wiped clean with absorbent cotton. Then, the tape stripping method was used to determine the content of dendrobium polysaccharide in the stratum corneum. 21 layers of skin on the surface of the pigskin were taped with 3M tape, the first layer was discarded, and the remaining 20 layers were placed in a 15mL centrifuge tube. 2mL of isopropanol was first added to the tube, ultrasonicated for 30 minutes, and centrifuged at 5000rpm for 30 minutes. The supernatant was filtered with a 0.22μm organic filter membrane, and the content of dendrobium polysaccharide was determined, which was the content of dendrobium polysaccharide in the stratum corneum.
[0071] The remaining skin surface was heated at 60 ° C for 15 s, and the viable epidermis was carefully cut off with a scalpel, cut into pieces and placed in a 15 mL centrifuge tube, 2 mL of isopropanol was added, ultrasonicated for 30 min, and centrifuged at 5000 rpm for 30 min. The supernatant was filtered with a 0.22 μm organic filter membrane and the content of ergothioneine was determined, which was the content of ergothioneine in the viable epidermis.
[0072] The remaining skin was cut into pieces and placed in a 15 mL centrifuge tube, 2 mL of isopropanol was added, and the mixture was ultrasonicated for 30 min, and then centrifuged at 5000 rpm for 30 min. The supernatant was filtered with a 0.22 μm organic filter membrane to determine the content of ergothioneine, which was the content of ergothioneine measured in the dermis.
[0073] The content of ergothioneine was determined by high performance liquid chromatography.
[0074] The results of the transdermal test were as follows Figure 4 As shown, it can be seen from the results that, whether in the active epidermis or the dermis, the transdermal effect of the ergothioneine lamellar liquid crystal nanocomposite is greatly improved compared with the ergothioneine aqueous solution. The system effectively improves the transdermal absorption effect of the active substance ergothioneine and improves its bioavailability.
[0075] Example 4
[0076] Anti-aging efficacy test:
[0077] Sample 1 Retinol DMSO solution (5% by mass) Sample 2 Ergothioneine aqueous solution (mass fraction 0.1%) Sample 3 Sample 1 in the embodiment
[0078] Test method:
[0079] The cell safety test verified that the above samples were non-cytotoxic at a concentration of 50 ppm, and the following experiments all used 50 ppm as the test concentration.
[0080] Cell inoculation: HFF-1 cells were grown in complete medium (high-glucose DMEM medium containing 10% FBS and 1% double antibody). The cells were digested with trypsin for 1 min (depending on the activity of trypsin, digested until the cells were visible to the naked eye) and then 1×10 5Each well was inoculated with 2 mL of cells / well in a 6-well plate and cultured in a 37°C, 5% CO2 incubator for 24 h.
[0081] UVA stimulation: Wash with PBS 3 times, add 2 mL PBS, 30 J / cm 2 After UVA irradiation, PBS was aspirated, 2 mL of DMEM or 50 ppm sample prepared with 2 mL of DMEM was added, and the cells were incubated in an incubator for 24 h.
[0082] The culture fluid was collected and assayed using an Elisa kit.
[0083] The results of the measurement can be found in Figure 5 The results showed that compared with the NC group (UVA model group), the above three samples can make damaged cells produce type I collagen. Among them, the content of type I collagen produced by sample 3 (lamellar liquid crystal nanocomposite) is more than twice that of the reference sample (sample 1 or 2).
[0084] Example 5
[0085] Essence formula:
[0086]
[0087]
[0088] The essence was divided into room temperature samples, heat-resistant samples, cold-resistant samples and light samples. The room temperature samples were placed away from light, the heat-resistant samples were placed in a constant temperature oven at (50±1℃), the cold-resistant samples were placed in a -18℃ refrigerator, and the light samples were placed in an artificial intelligence climate box. After 3 months, the sample properties, appearance, color and smell were observed. There was no oil-water separation phenomenon. The results are shown in the following table.
[0089] Formula stability test:
[0090]
[0091] The experimental results show that after the sample provided by the present invention is compounded with the matrix, no obvious discoloration and stratification phenomenon occurs after being placed at room temperature, high temperature, low temperature and light for 3 months, which can meet the actual application needs.
[0092] Example 6
[0093] Human efficacy test:
[0094] Sample: the essence in Example 5.
[0095] Purpose of test: Single-center open trial, through instrument testing method after more than 30 people use the product, before and after comparison, to verify the anti-aging, hydrating and moisturizing effects of the essence.
[0096] Experimenters: This test includes 30 healthy female subjects aged 20-50 years old, preferably volunteers with slight fine lines, dry lines or obvious wrinkles.
[0097] Test method:
[0098] Before and after comparison, the volunteers' faces were tested before use, 30 minutes after use, 4 hours after use, and 14 days after use. The test items included facial skin stratum corneum water content, facial skin transepidermal water loss, facial skin firmness, and skin wrinkle ratio. How to use the essence: The tester applied the essence on the face once in the morning and once in the evening.
[0099] Test instrument: Multi-probe skin test system (Courage & Khazaka, Germany):
[0100] Moisture Corneometer probe - tests the moisture content of the facial skin stratum corneum;
[0101] Tewameter probe for transepidermal water loss: tests transepidermal water loss on the face;
[0102] Elastic Cutometer probe - tests facial skin firmness;
[0103] Visia-CR Skin Detector (Canfield, USA) – tests the percentage of skin wrinkles;
[0104] Test results:
[0105] Hydration and moisturizing test results:
[0106]
[0107] Transepidermal water loss test results:
[0108]
[0109] Tightness test results:
[0110]
[0111]
[0112] Wrinkle test results:
[0113]
[0114] The results showed that the essence has strong immediate and long-lasting anti-wrinkle ability, and strong long-lasting moisturizing and firming ability.
[0115] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A layered liquid crystal nanocomposite with multiple anti-aging effects, characterized in that: The total weight of the raw materials of the composition is 100%, comprising: Glycolipid emulsifier 0.1%-20%; Amino acid emulsifier 0.1%-5%; Retinol and its derivatives 0.1%-5%; Water-soluble active ingredients 0.01%-5%; Ceramide NP 0.01%-1%; Oil 10%-20%; Polyol 30%-50%; Make up to 100% with water.
2. The lamellar liquid crystal nanocomposite according to claim 1, wherein: The glycolipid emulsifier includes one or more of mannosyl erythritol lipid, cellobiose lipid, disaccharide diglyceride, monoacylglycerol, and galactosyl diglyceride.
3. The lamellar liquid crystal nanocomposite according to claim 1 or 2, characterized in that: The water-soluble active ingredients include one or more of ergothioneine, β-nicotinamide mononucleotide, pyrroloquinoline quinone, and α-ketoglutaric acid.
4. The lamellar liquid crystal nanocomposite according to claim 3, wherein: The amino acid emulsifier includes one or more of phytosterol / behenyl alcohol / octyldodecyl lauroyl glutamate, phytosterol / octyldodecyl lauroyl glutamate, cholesterol / behenyl alcohol / octyldodecyl lauroyl glutamate, cholesterol lauroyl glutamate, di(lauroyl glutamine) sodium lysine, di(octyldodecyl polyether-5) lauroyl glutamate, and dioctyldodecyl lauroyl glutamate.
5. The lamellar liquid crystal nanocomposite according to claim 1 or 4, characterized in that: The polyol includes one or more of propylene glycol, butylene glycol, hexylene glycol, pentylene glycol, glycerol and sorbitol.
6. The lamellar liquid crystal nanocomposite according to claim 5, characterized in that: The retinol and its derivatives include one or more of retinol, retinol palmitate, retinol propionate, retinol acetate, retinol retinoic acid ester, and hydroxypinacolone retinoic acid ester.
7. The lamellar liquid crystal nanocomposite according to claim 6, wherein: The oil comprises one or more of behenyl alcohol, cetearyl alcohol, squalane, caprylic capric triglyceride and octyldodecanol.
8. The method for preparing the lamellar liquid crystal nanocomposite according to any one of claims 1 to 7, characterized in that: include, Retinol and its derivatives, ceramide NP, and oil are mixed, dissolved and stirred evenly at 80-90° C. to obtain phase A; Mix the glycolipid emulsifier, amino acid emulsifier, water-soluble active ingredient, polyol and water, dissolve and stir evenly at 80-90° C. to obtain phase B; Phase B and phase A are mixed evenly, maintained at 80-90° C., stirred at 15000 rpm for initial emulsification, and then high-pressure homogenization is performed at a pressure of 800 bar for 4-5 times to obtain a lamellar liquid crystal nanocomposite.
9. Use of the lamellar liquid crystal nanocomposition with multiple anti-aging effects as claimed in any one of claims 1 to 7 in cosmetics.
10. The use according to claim 9, characterized in that: The cosmetics are selected from one or more of facial cleansers, facial masks, lotions or emulsions, creams, and essences.
Citation Information
Cited By
Anti-aging composition and application and product thereof
CN121714467A